Improving Biological Treatment of Real Bilge Wastewater With Zero Valent Iron and Activated Charcoal Addition - Mazioti, Aikaterini A.; Notarides, Gregoris; Symeou, Giannis; Vyrides, Ioannis (Frontiers in Bioengineering and Biotechnology, 2020)
From the ships engine rooms a recalcitrant wastewater is produced called “bilge” which contains oil, metal working fluids, surfactants and salinity. This study investigated the treatment of real bilge wastewater in short experiments using the following processes: i) anaerobic digestion with granular sludge and ZVI addition for enhancement of methane production, ii) activated charcoal addition to biological treatment (aerobic and anaerobic) for Chemical Oxygen Demand (COD) significant reduction and iii) combination of ZVI and anaerobic charcoal addition for high performance treatment. The addition of ZVI in anaerobic sludge resulted in higher performance mostly in cumulative CH4 production. The microbial profile of anaerobic granular sludge exposed to ZVI was determined and Acetobacterium and Arcobacter were the most dominant bacteria genera. Activated charcoal achieved higher COD removal, compared to biological degradation (aerobic and anaerobic). The combination of the two mechanisms, activated charcoal and biomass, had higher COD removal only for aerobic biomass. The combination of ZVI and activated charcoal to anaerobic digestion resulted in higher CH4 production and significant COD removal in short contact time.